1990
DOI: 10.1172/jci114622
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of recombinant human monocyte-derived interleukin 1 receptor antagonist.

Abstract: Human monocytes cultured on adherent IgG produce a specific IL-1 inhibitor that functions as a receptor antagonist (IL-ira). This molecule has been purified, sequenced, cloned as a cDNA, and expressed in Escherichia coli. Recombinant IL-ira has 17,000 mol wt and binds to IL-i receptors on T lymphocytes, synovial cells, and chondrocytes with an affinity nearly equal to that of IL-1. These studies have examined some biological properties of purified recombinant human IL-ira. This protein exhibits a dose-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
221
1
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(248 citation statements)
references
References 22 publications
19
221
1
4
Order By: Relevance
“…Our daia support the study produced by Arend et ai, who found inhibition by hrlL-IRa of another arachidonic acid metabolite, a cyciooxygenase product, PGE2 [22]. The mechanism and the molecular changes that occur in the human monocyte.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our daia support the study produced by Arend et ai, who found inhibition by hrlL-IRa of another arachidonic acid metabolite, a cyciooxygenase product, PGE2 [22]. The mechanism and the molecular changes that occur in the human monocyte.…”
Section: Discussionsupporting
confidence: 89%
“…wt 22000 (glycosylated form) and 17000 (non-glycosylaled form), could theoretically interfere with any one of these steps [19,20]. IL-!Ra is secreted by human monocyles and is structurally similar to IL-1/f (26' Vi> amino acid homology) and IL-la (19% homology), but with no iL-l-like aetivity [21][22]. IL-lRa is a natural inhibitor of IL-I and is capable of inhibiting eyelooxygenase and down-regulating DNA synthesis in mitogen-stimulated lymphoeytes.…”
Section: Introdlfctionmentioning
confidence: 99%
“…However, it remains unclear whether sIL-1ra can directly regulate the level of ICE gene expression before it is secreted or some other co-factors play a crucial role in ICE regulation at the transcription level of sIL-1ra, and the further study will be needed to clarify this mechanism. It is well known that a 10-to 100-fold molar excess of IL-1ra is often required to inhibit IL-1 activity (Arend et al, 1990). In the present study, we found that IL-1ra/IL-1β ratios in the supernatants were less than 10 in , while those were more than 10 in KU-1 and KU-2.…”
Section: Figuresupporting
confidence: 50%
“…These doses of individual factors were within the range between effective dose 75 and effective dose 100 of their proper effects on chondrocytes, according to dose-response curves in the previous reports (11,12,15,16,(21)(22)(23)(24)(25)(26)(27)(28) cells in 5 l of 0.8% atelocollagen gel) were cultured in Dulbecco's modified Eagle's medium/F-12 containing the combinations for 2 weeks, and the GAG accumulation was measured as described below. Parameter estimates of the GAG accumulation by one factor or two were calculated from the F values that represent the effects of the individual factors and the interaction terms of two factors by the analysis of variance using the software above.…”
Section: Methodsmentioning
confidence: 57%